Intrinsic Square Functions and Commutators on Generalized Morrey Spaces Associated with Ball Banach Function Spaces (Analysis in Theory and Applications, 2025)
In this paper, the authors study the boundedness for a large class of intrinsicsquare functions and their commutators on generalized Morrey spaces associated withball Banach function spaces, respectively.
Keywords: Intrinsic square function; commutator; generalized Morrey space; ball Banach function space.